Arthroplasty for major defects of articular areas of fingers - Brozman, M; Jakubovský, J (Acta chirurgiae plasticae, 1990)
The costal perichondrium is a suitable material for the reconstruction of major damage to articular areas, even bone tissue in small joints of the hand. A modelled silicone implant conditions and simultaneously defines the shape of the reconstructed areas. Together with the perichondrium reconstruction, it helped to fill the defect and for a suitable shape of the articular areas. Morphological findings of the perichondrium transformation showed a steady growth and a rising frequency of hyalinization of larger foci containing chondrocyte-like cells. After 8 years the cartilage surface showed a thick layer of hyaline cartilage.
Keywords: Finger Injuries; Prostheses and Implants; artroplastika; Metacarpophalangeal Joint; následné studie; lidé; protézy a implantáty; ankylóza; Follow-Up Studies; poranění prstů ruky; Arthroplasty; metakarpofalangeální kloub; Humans; Ankylosis